An algorithm to improve consistency in Smoothed Particle Hydrodynamics. (2nd September 2015) - Sibilla, Stefano
Highlights: An algorithm to improve the accuracy of derivatives in 1D SPH is proposed. A linear system for the first 3 derivatives is solved at each particle location. Second-order consistency on the first derivative is obtained everywhere. First-order consistency on the second derivative is obtained everywhere. Tests on Burgers equation confirm applicability to convection–diffusion problems. Abstract: An algorithm to improve the numerical evaluation of derivatives of a field function in Smoothed Particle Hydrodynamics is proposed. The algorithm is based on the solution, at each particle location, of a linear system whose unknowns are the first three derivatives of the desired function; the coefficients of the linear system are obtained from various possible particle approximations of the Taylor series expansion of the function. The method proves to be 2nd-order consistent for the 1st derivatives and 1st-order consistent for the 2nd derivatives, both inside the domain and close to the boundaries, and it is not affected by an irregular particle distribution. A numerical test performed on the SPH solution of the viscous Burgers equation proves that the method can be validly applied to the simulation of convection–diffusion problems.